Enriching a protein drink with leucine augments muscle protein synthesis after resistance exercise in young and older men - Atherton, Philip J.; Kumar, Vinod; Selby, Anna L.; Rankin, Debbie; Hildebrandt, Wulf; Phillips, Bethan E.; Williams, John P.; Hiscock, Natalie; Smith, Kenneth (Elsevier, 2016)
Maximizing anabolic responses to feeding and exercise is crucial for muscle maintenance and adaptation to exercise training. We hypothesized that enriching a protein drink with leucine would improve anabolic responses to resistance exercise (RE: 6×8 knee-extension repetitions at 75% of 1-RM) in both young and older adults. Groups (n=9) of young (24±6 y, BMI 23±2kg.m-2) and older men (70±5 y, BMI 25±2 kg.m-2) were randomized to either: (i) RE followed by Slim-Fast Optima (SFO 10 g PRO; 24 g CHO) with 4.2 g of leucine (LEU) or, (ii) RE+SFO with 4.2 g of alanine (ALA; isonitrogenous control). Muscle biopsies were taken before, immediately after, and 1, 2 and 4 h after RE and feeding. Muscle protein synthesis (MPS) was measured by incorporation of [1, 2-13C2] leucine into myofibrillar proteins and the phosphorylation of p70S6K1 by immunoblotting. In young men, both area under the curve (AUC; FSR 0-4 h P<0.05) and peak FSR (0.11 vs. 0.08%.h.-1; P<0.05) were greater in the SFO+LEU than in the SFO+ALA group, after RE. Similarly, in older men, AUC analysis revealed that post-exercise anabolic responses were greater in the SFO+LEU than SFO+ALA group, after RE (AUC; FSR 0-4 h P<0.05). Irrespective of age, increases in p70S6K1 phosphorylation were evident in response to both SFO+LEU and SFO+ALA, although greater with leucine supplementation than alanine (fold-change 2.2 vs. 3.2; P<0.05), specifically in the older men. We conclude that addition of Leucine to a sub-maximal PRO bolus improves anabolic responses to RE in young and older men.